Hydroxynonenal causes Langerhans cell degeneration in the pancreas of Japanese macaque monkeys. - Piyakarn Boontem (Public Library of Science (PLoS), 2021)
Background For their functions of insulin biosynthesis and glucose- and fatty acid- mediated insulin secretion, Langerhans β-cells require an intracellular milieu rich in oxygen. This requirement makes β-cells, with their constitutively low antioxidative defense, susceptible to the oxidative stress. Although much progress has been made in identifying its molecular basis in experimental systems, whether the oxidative stress due to excessive fatty acids plays a crucial role in the Langerhans cell degeneration in primates is still debated. Methods Focusing on Hsp70.1, which has dual functions as molecular chaperone and lysosomal stabilizer, the mechanism of lipotoxicity to Langerhans cells was studied using macaque monkeys after the consecutive injections of the lipid peroxidation product 'hydroxynonenal'. Based on the 'calpain-cathepsin hypothesis' formulated in 1998, calpain activation, Hsp70.1 cleavage, and lysosomal integrity were studied by immunofluorescence histochemistry, electron microscopy, and Western blotting. Results Light microscopy showed more abundant vacuole formation in the hydroxynonenal-treated islet cells than the control cells. Electron microscopy showed that vacuolar changes, which were identified as enlarged rough ER, occurred mainly in β-cells followed by δ-cells. Intriguingly, both cell types showed a marked decrease in insulin and somatostatin granules. Furthermore, they exhibited marked increases in peroxisomes, autophagosomes/autolysosomes, lysosomal and peroxisomal membrane rupture/permeabilization, and mitochondrial degeneration. Disrupted peroxisomes were often localized in the close vicinity of degenerating mitochondria or autolysosomes. Immunofluorescence histochemical analysis showed an increased co-localization of activated μ-calpain and Hsp70.1 with the extralysosomal release of cathepsin B. Western blotting showed increases in μ-calpain activation, Hsp70.1 cleavage, and expression of the hydroxynonenal receptor GPR109A. Conclusions Taken together, these data implicate hydroxynonenal in both oxidation of Hsp70.1 and activation of μ-calpain. The calpain-mediated cleavage of the carbonylated Hsp70.1, may cause lysosomal membrane rupture/permeabilization. The low defense of primate Langerhans cells against hydroxynonenal and peroxisomally-generated hydrogen peroxide, was presumably overwhelmed to facilitate cell degeneration.